Testing the Role ESG as Moderator: When Financial Ratios Meet Tobin's Q - Harold Kevin Alfredo; Afit Afrizal; Muhammad Irfan Pratama; Hiro Sejati (UNIVED Press, 2026)
This study seeks to evaluate the role of ESG as a moderating variable concerning the relationship between financial ratios and firm value, which is assessed using Tobin's Q. The analysis focuses on companies listed in the 2025 Morningstar Sustainalytics ranking. The independent variables include key financial ratios liquidity, profitability, and leverage extracted from firms’ 2024 financial statements. ESG risk ratings are employed as the moderating variable, while Tobin’s Q serves as the dependent variable. The findings indicate that profitability has a positive and significant impact on firm value, whereas liquidity and leverage exhibit no statistically meaningful effects. Furthermore, the results show that ESG risk does not moderate the relationships between liquidity or leverage and firm value. However, ESG risk is found to weaken the positive relationship between profitability and firm value, with significance at the 10% level. Overall, the results align with signaling theory, suggesting that the strength of financial signals can diminish when unfavourable non-financial signals, such as high ESG risk, are present.